(3LgGR dbjGS OQLI GdERGMI GdCeGejI dYXe GdbUHI ddhbGjI ef EUGHI GdQHGW GdUdjHj GdCeGejs - (3YeQh eMeO EHQGgje(B, (3MSfjfs ((3GdGScfOQjI(B:s (3eDSSI YGde GdQjGVI ddfTQ(B;(3OGQ GdhaGA dOfjG GdWHGYI h GdfTQ(B,s, 2017)
(3JUeje LgGR ebJQM dbjGS OQLI GdCRGMI GdCeGcjI h GdbhI GdeSJNOI aj GdERGMI GdGeGejI dYXe GdbUHI cCMO eJWdHGJ GdhbGjI ef EUGHI GdQHGW GdUdjHj GdGeGej MjK Je JfGhd GdJQcjH GdJTQjMj deaUd GdQcHI h BdjI YedgG h cPG GdJQcjH GdJTQjMj ddQHGW GdUdjHj GdGeGej h BdjI Yedg h EUGHJg h JTNjUgG h eJWdHGJ GdhbGjI ef gPg GdGUGHI h cPG CLgRI bjGS OQLI GdGRGMI GdCeGejI dYXe GdbUHIceG Je GdJWQb Gdi JMdjd HYV GdOQGSGJ GdeQLYjI h GdGSJaGOI efgG h bO Je GSJNOGe GdefgL GdhUaj h GdefgL GdJLQjHj eY JfGhd YQV h TQM dLejY GLRGA GdLgGR GdQFjSjI h NWhGJ JTZjdg h EecGfjGJ h bOQGJ gPG GdLgGR h WQjbI MSGH fJGFLg h CNjQG GdGSJNdGUGJ h GdJhUjGJ (B.s
(3eQGLY U(B.229 (3edGMb U(B.215s
Keywords: (3EUGHGJ GdedGYHs; (3QaY GdGKbGd (B- (3GUGHGJs; (3cQI GdSdI (B- (3GUGHGJs